2010
DOI: 10.1021/bc100351n
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Modification of Turnip Yellow Mosaic Virus by Cu(I) Catalyzed Azide−Alkyne 1,3-Dipolar Cycloaddition Reaction and Its Application in Cell Binding

Abstract: Turnip yellow mosaic virus (TYMV) is an icosahedral plant virus with a diameter of 28-30 nm that can be isolated in gram quantities from turnip or Chinese cabbage inexpensively. In this study, TYMV combined with spatially addressable surface chemistries was selected as a prototype bionanoparticle for modulating patterns of cell adhesion, morphology, and proliferation. We exploited the chemical reactivity of TYMV using the mild conditions of Cu(I) catalyzed azide-alkyne cycloaddition (CuAAC) reaction, the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Additionally, the RGD ligand density and its spatial arrangement could play a significant role during the binding process [36]. Another difference from previously reported results [21,28] was that the HeLa cells did not present similar elongated or stretched morphologies to those of NIH3T3 fibroblasts on APTES slides. This might be attributable to the different properties of these two cell types and their interactions with the APTES ligand on the slides.…”
Section: Cell Adhesion With Hela Cellsmentioning
confidence: 81%
See 3 more Smart Citations
“…Additionally, the RGD ligand density and its spatial arrangement could play a significant role during the binding process [36]. Another difference from previously reported results [21,28] was that the HeLa cells did not present similar elongated or stretched morphologies to those of NIH3T3 fibroblasts on APTES slides. This might be attributable to the different properties of these two cell types and their interactions with the APTES ligand on the slides.…”
Section: Cell Adhesion With Hela Cellsmentioning
confidence: 81%
“…The reactivity of the CCMV carboxyl groups was tested with fluorescein cadaverine under activation with EDC and sulfo-NHS, which revealed that 560 carboxylates were modified in high yields [12]. This was approximately 4.7 6 .2 times higher than that accessible in TYMV (90 ~ 120 carboxylic groups) [21]. To explore the potential of introducing a multifunctional group onto the surface of CCMV, the viral capsids were labeled with acetylene at surface-exposed carboxylic groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Formation of PVN films by these methods is predominantly controlled by the concentration of PVN and the strength of its surface attraction (Barick and Bahadur, 2010;Evans, 2008). The uniform and multivalent nature of these PVN coated surfaces has led to investigation into their effects on cell responses and differentiation (Kaur et al, 2010a(Kaur et al, , 2010bZan et al, 2012;Zeng et al, 2011). Using Turnip yellow mosaic virus (TYMV) as a scaffold for the multivalent display of the cell adhesion peptide RGD, Zan et al demonstrated enhanced mesenchymal stem cell adhesion and spreading onto surfaces layered with TYMV genetically programed to display the RGD peptide (Zan et al, 2012).…”
Section: Two-dimensional Surface Assembliesmentioning
confidence: 99%